PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. WARTA MEDIA NUSANTARA TRIBUN JATENG - Muhammad Agung Baiquni; Apriatni Endang Prihatini (Jurnal Ilmu Administrasi Bisnis, 2016)
Organizational culture and work environment is a for factor the achievement of a good employee performance. PT. Warta media nusantara tribun jateng is a company engaged in the publication of the regional newspaper in the city of semarang with the aim of providing information to the public through the mass media. To improve the quality of human resources and the achievement of business objectives of the company, then an increase in employee performance can be done by strengthening the organizational culture and to build a good working environment.This research use eksplanatory research, the population used as samples by using the with amount of 71 employees in PT. Warta media nusantara tribun jateng. By using questionnaire and measurement scale likert technique as well as with the calculation of the correlation, simple and multiple regression using SPSS 20.0.This research concluded that the organizational culture and work environment affects employee performance, either partially or simultaneously. Variable organizational culture has a graeter influence than environment variables work. Suggestion for PT. Warta media Nusantara tribun jateng is preferably gatherings often do together and also conduct training, so that concern for a fellow employee can run well and be able to achive the objectives of the company. In addition it provides a more complete work equipment as well as adding an air conditioner in order to make workers more comfortable in this work.